2021
DOI: 10.5902/1984644466423
|View full text |Cite
|
Sign up to set email alerts
|

Digital competence of teachers and students in Yakutia: problems and prospects of e-learning during the pandemic

Abstract: RESUMOSob medidas de auto-isolamento e quarentena durante a pandemia COVID-19 em 2020, o ensino à distância é urgente em todos os níveis educacionais. Esses eventos afetaram a competência digital de professores e alunos de especialidades pedagógicas que lecionam para alunos e escolares. O artigo analisa as competências digitais necessárias para um professor moderno implementar com sucesso as necessidades educacionais dos alunos ao usar tecnologias de ensino à distância e elearning. O objetivo da pesquisa é aum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 5 publications
1
3
2
1
Order By: Relevance
“…However, the results for H2 revealed that digital technical competence had a positive but insignificant influence on lecturers' self-efficacy in online classes. Nonetheless, this finding is contrary to the findings of previous scholars (Adiyarta, 2018;Basantes-Andrade et al, 2020;Baroudi & Shaya, 2022;Mailizar & Fan, 2020;Liu et al, 2022;Sorochinsky, 2021), who all indicated that the relationship was positive and significant. However, it can be inferred that, in the context of the study, digital technical competence was not very imperative for lecturers' self-efficacy in online classes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the results for H2 revealed that digital technical competence had a positive but insignificant influence on lecturers' self-efficacy in online classes. Nonetheless, this finding is contrary to the findings of previous scholars (Adiyarta, 2018;Basantes-Andrade et al, 2020;Baroudi & Shaya, 2022;Mailizar & Fan, 2020;Liu et al, 2022;Sorochinsky, 2021), who all indicated that the relationship was positive and significant. However, it can be inferred that, in the context of the study, digital technical competence was not very imperative for lecturers' self-efficacy in online classes.…”
Section: Discussioncontrasting
confidence: 99%
“…However, there are limitations that emerged that can be addressed by future research. For instance, contrary to Adiyarta (2018), Basantes-Andrade et al ( 2020), Baroudi and Shaya (2022), Mailizar andFan (2020), andSorochinsky (2021), this study reported that digital technical competence of lecturers insignificantly contributed to their self-efficacy in online classrooms. Therefore, future researchers should further test this hypothesis to confirm or disconfirm its authenticity in the context of universities in Uganda.…”
Section: Limitationscontrasting
confidence: 86%
“…These cover pedagogical design, rubrics development, collaboration tools, monitoring, and online resources for educational purposes. Corollary to this, [41] identified prospects of e-learning as the study outcomes revealed an increased efficiency of work for both teachers and students when refresher courses that support e-learning implementation. Hence, with the perceived digital competence are the identified support and resources to withstand the requirements of delivering flexible learning options to the pre-service teachers.…”
Section: B Discussionmentioning
confidence: 82%
“…Additionally, strong relationships with stakeholders, including partners, regulators, and those affected by the implementation, are crucial for effective implementation (Plaza-Úbeda et al, 2010). Several scholars (e.g., Adiyarta et al, 2018;Ati et al, 2021;Basantes-Andrade et al, 2020;Hatlevik & Hatlevik, 2018;Kamasak, 2017;Kong, 2019;Sorochinsky, 2021;Twinamasiko et al, 2021;Trivedi & Patel, 2020;Ünal, 2020) have explored the relationship between intangible resources and e-learning. However, these studies have primarily focused on contexts outside of Uganda, leaving the opinions of those involved in e-learning implementation in the local context unexplored.…”
Section: Schools' Intangible Resources and E-learning Implementationmentioning
confidence: 99%